Simulating Artificial 1D Physics with Ultra‐Cold Fermionic Atoms: Three Exemplary Themes. Issue 6 (19th May 2020) - Dobrzyniecki, Jacek; Sowiński, Tomasz
Abstract: For over twenty years, ultra‐cold atomic systems have formed an almost perfect arena for simulating different quantum many‐body phenomena and exposing their non‐obvious and very often counterintuitive features. Thanks to extremely precise controllability of different parameters they are able to capture different quantum properties which were previously recognized only as theoretical curiosities. Herein, the current experimental progress in exploring the curious 1D quantum world of fermions is traced from the perspective of three subjectively selected trends being currently under vigorous experimental validation: i ) unconventional pairing in attractively interacting fermionic mixtures, ii ) fermionic systems subjected to the artificial spin‐orbit coupling, iii ) fermionic gases of atoms with high SU ( N ) symmetry of internal states. Abstract : Ultra‐cold atomic systems are an excellent arena for simulating quantum many‐body phenomena. The current experimental progress in exploration of 1D ultra‐cold fermionic systems is reviewed from the perspective of three subjectively selected trends of high experimental interest: unconventional pairing in attractively interacting mixtures, systems subjected to artificial spin–orbit coupling, and atomic gases with a high symmetry of internal states.